Pendekatan Parodi, Simbolik dan Metafora pada Karya Seni Jogja International - Sari Wulandari (Bina Nusantara University, 2013)
Ngayogyakarta Negari Exhibition 2012 is part of the Festival of Arts 2012 Ngayogyakarta Hadiningrat Negari held in commemoration of the 2.5-century founding of Ngayogyakarta and 100 years of the birth of Sri Sultan Hamengkubuwono IX, followed by 124 artists Yogyakarta, both painting, photography, sculpture, audio visual, and installation as well which displayed the works of Sri Sultan Hamengkubuwono IX and Yogyakarta themed. Jogja International work sculpture by sculpture artist, Dunadi, is one of the few works of sculpture on display in this activity, similar to superhero Spider-Man but wearing blangkon and sarong. In addition to its large size and white color, which makes it interesting sculpture to be observed, studied and discussed is this artwork has conveyed symbolic, metaphoric, and typical parodik messages of Yogyakarta people. This discussion was done through art criticism and aesthetic theory in which the implementation of theories is very broad in the domain art and design. Although the artwork discussed did not pertain directly to the the domain of Visual Communication Design, sensitivity to social issues, creative approach, and beautiful execution Dunadi artist was expected to add experience and insight into the art of the artists and designers in Indonesia.